Euphemisms in Modern Political Discourse: Joseph Biden’s Speeches in the War in Uk - Nataliia M. Tymoshchuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Euphemism occupies a central place in political discourse. The article aims to probe into the rhetorical device of euphemism in the political discourse of the 46th President of the United States, Joseph Biden, during the Ukrainian-Russian war. The significance of the study is based on the necessity to research the linguistic image of the Russian-Ukrainian war and its main political actors in current political discourse. The relevance of this study is also determined by the aim to show the use of euphemisms in current political discourse on the example of Joseph Biden’s speeches. The research methods of the article combine continuous sampling, component analysis; comparison and observation, classification and systematization of data, quantitative calculations, etc. The also study employs Multimodal Discourse Analysis (MDA) which explores the relations between language and power as well as the relations between language and image. Our research limits its analysis of multimodality to two modalities, gesture and speech. President Joseph Biden’s speeches on the United Efforts of the Free World to Support the People of Ukraine (February 26, 2022) and on the One-Year Anniversary of Russia’s Brutal and Unprovoked Invasion of Ukraine of the US (February 21, 2023) at the Royal Castle in Warsaw serve as a material for the study of euphemisms in political discourse. Conclusions. Euphemism is a characteristic element of political discourse. The role of euphemisms in political discourse is primarily determined by the desire for politically correct intercultural communication, politeness and tolerance, and mutual understanding. Euphemisms express the moral values of society and help to overcome intercultural barriers. The analysis of Joseph Biden’s political speeches made it possible to identify groups of the most commonly used types of euphemisms, namely, concealment of military conflicts (“conflict”, “invasion”, “aggression”, “fight for freedom”, “crisis”, “the great battle for freedom”); taboo of death (“sacrifice”, “pass away”, “lose their lives”); socio-economic sphere (“the continued support”, “support”). According to research data, 47.2% of euphemisms have a veiling function, 38.9% of euphemisms perform a cooperative function and 8.3% of euphemisms have a preventive function in Joseph Biden’s speeches. We suggest Joseph Biden delivers the same viewpoint across his gestures and speeches. Analyzing the gesture-euphemism correlation, we conclude that the 46th US President mainly employed these gestures with integrative and complementary functions. The present paper shows how the polyphonic self of the US political leader is conveyed not solely through speech, but also through gesture. Thus, we assume that the driving force in the evolution of the politician’s polyphonic self is the distribution of viewpoints across modalities of political discourse, where they influence each other in live communication. Biden’s speech is characterized by a short syntagm, as he slows down the pace, trying to convey every word to the audience. The stress is mostly emphatic, with emphasis created by increasing pitch, volume, and duration. Pauses, intonations, voice, register, and tone of speech, being a frame of euphemistic connotations, form the specificity of the communicative and pragmatic field of audiovisual narrative.